On Earth as it is in Heaven: Healing through Forgiveness - Griffin, Brandon J. (Journal of psychology and theology, 2014)
In this article, we hypothesize that health outcomes associated with forgiveness, if it is received from God, others, or oneself or if it is granted to others, foreshadow the eschatological regeneration of Christians. Over a decade of scientific inquiry supports a working model that integrates forgiveness, health, and Christian (primarily Reformed) theology. To support this model, we examined studies, reviews of scientific literature, and theological sources to adduce relevant evidence according to four areas of forgiveness—by God, others, or oneself and granted to others. We thus identify domains in which God's promise of forgiveness and Christians’ ministry of forgiveness to others might be associated with improved mental and physical health outcomes. In this way, the healing effects associated with forgiveness ultimately function as a glimpse of God's redemptive plan for humankind.